(meth) acryloyl group-containing polycarboxylic acid compound, heat-conducting composition, and heat-conducting sheet
By combining the (meth)acryloyl group-containing polycarboxylic acid compound with other components, a high heat conductivity and low thermal resistance heat conduction composition and heat conduction sheet are formed, and the problem of the reduction of the bonding strength of the existing heat conduction materials at high temperatures is solved, and efficient heat conduction and welding effects are achieved.
Patent Information
- Application Number
- CN202380063414.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-05
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-11
AI Technical Summary
When the heating temperature of the existing heat conducting materials exceeds the melting point of the thermoplastic resin, the bonding strength is greatly reduced, and the curing reaction is restricted by the molecular structure of the oxetane compound, resulting in a decrease in bonding strength.
A (meth)acryloyl group-containing polycarboxylic acid compound is used to form a heat conduction composition and a heat conduction sheet with high thermal conductivity and low thermal resistance by combining with a curing component, a free radical polymerization initiator, a heat conduction particle and a low melting point metal particle.
It achieves high bonding strength and good welding effect, and has high thermal conductivity and low thermal resistance, which is suitable for preventing the heating of electronic components such as LSI.
Smart Images

Figure CN119816483A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a (meth)acryloyl group-containing polycarboxylic acid compound, a thermally conductive composition and a thermally conductive sheet. Background Art
[0002] In LSI (large scale integration) and other electronic devices, due to the heat generated by the components used, when the LSI itself is exposed to high temperatures for a long time, it may be accompanied by malfunction and failure. Therefore, in order to prevent the temperature of LSI and the like from rising, heat conductive materials are widely used. The heat conductive materials can prevent the temperature of the machine by diffusing the heat generated by the components or conducting it to the heat dissipation components for dissipating it to the outside of the system such as the atmosphere.
[0003] When metal or ceramic is used as such a heat conducting material, there are problems such as difficulty in weight reduction, poor processability, or low flexibility. Therefore, various heat conducting materials using polymer materials such as resins and rubbers as base materials have been proposed. For example, a resin composition is proposed, comprising (A) a polymer compound having one or more structures selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule, (B) an epoxy resin, (C) a thermally conductive filler, and (D) an active ester curing agent, wherein the component (A) is one or more selected from a resin having a number average molecular weight (Mn) of 1,000 to 1,000,000 or a glass transition temperature (Tg) of 25°C or less and a resin that is liquid at 25°C, and the content of the component (A) is 10% by mass to 65% by mass when the resin component is 100% by mass, and the content of the component (C) is 85% by mass or more when the non-volatile components of the resin composition are 100% by mass (see, for example, Patent Document 1).
[0004] [Prior art literature]
[0005] [Patent Literature]
[0006] [Patent Document 1] Patent No. 6787210 Summary of the invention
[0007] [Problems to be solved by the invention]
[0008] In the technology described in the above Patent Document 1, a thermoplastic resin is used as a base polymer, so when the heating temperature exceeds the melting point of the thermoplastic resin, there is a problem of a significant decrease in bonding strength. In addition, the curing reaction of the oxetane compound and the polycarboxylic acid as the curing component is restricted by the molecular structure of the oxetane compound, and there is a concern that the bonding strength will decrease.
[0009] The present invention aims to solve the above-mentioned problems in the past and achieve the following objectives. That is, the present invention aims to provide a novel (meth)acryloyl group-containing polycarboxylic acid compound that can exhibit high bonding strength and good fluxing effect, and a thermally conductive composition and a thermally conductive sheet that contain the (meth)acryloyl group-containing polycarboxylic acid compound and can achieve high thermal conductivity and low thermal resistance.
[0010]
Methods to solve the problem
[0011] The means for solving the above-mentioned problems are as follows.
[0012] <1> A (meth)acryloyl group-containing polycarboxylic acid compound characterized by being represented by at least one of the following general formula (1) and the following general formula (2).
[0013]
Chemistry 1
[0014]
[0015] Here, in the general formula (1), R1 and R3 represent an alkylene group. R2 represents a single bond or an alkylene group. R4 represents an alkylene group. -OCO-A represents an acryloyl group or a methacryloyl group.
[0016]
Chemistry 2
[0017]
[0018] Here, in the general formula (2), R1 and R2 represent an alkylene group. R4 represents an alkylene group. R5 represents a hydrogen atom or an alkyl group. -OCO-A represents an acryloyl group or a methacryloyl group.
[0019] <2> According to the <1> The described (meth)acryloyl group-containing polycarboxylic acid compound, in the general formula (1), the R2 is a single bond, and the R1 and R3 are -CH2-.
[0020] <3> According to the <1> arrive <2> The (meth)acryloyl group-containing polycarboxylic acid compound described in any one of items, wherein R4 is ethylene.
[0021] <4> According to the <1> arrive <3> The (meth)acryloyl group-containing polycarboxylic acid compound according to any one of the above has flux activity.
[0022] <5> A heat conduction composition, characterized in that it contains <1> arrive <4> The (meth)acryloyl group-containing polycarboxylic acid compound according to any one of the above, a curing component, a radical polymerization initiator, thermally conductive particles, and low-melting-point metal particles.
[0023] <6> According to the <5> The heat conduction composition described above, wherein the content of the (meth)acryloyl group-containing polycarboxylic acid compound is 1 volume % or more and 10 volume % or less.
[0024] <7> According to the <5> arrive <6> The thermally conductive composition according to any one of the claims, wherein the curing component is at least one of an oxirane ring compound and an oxetane compound.
[0025] <8> According to the <5> arrive <7> The thermally conductive composition according to any one of claims , wherein the thermally conductive particles are at least one of copper particles, silver-coated particles, and silver particles.
[0026] <9> According to the <5> arrive <8> The thermally conductive composition according to any one of the claims, wherein the low melting point metal particles contain Sn and at least one selected from Bi, Ag, Cu and In.
[0027] <10> A heat conduction sheet, characterized in that it comprises <5> arrive <9> A cured product of the thermally conductive composition described in any one of the above.
[0028] [Effects of the Invention]
[0029] According to the present invention, the above-mentioned problems in the past can be solved, the above-mentioned objects can be achieved, and a novel (meth)acryloyl group-containing polycarboxylic acid compound that can exhibit high bonding strength and good fluxing effect, a thermally conductive composition containing the (meth)acryloyl group-containing polycarboxylic acid compound and capable of achieving high thermal conductivity and low thermal resistance and a thermally conductive sheet can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0030]
Figure 1
[0031] ((Meth)acryloyl group-containing polycarboxylic acid compound)
[0032] The (meth)acryloyl group-containing polycarboxylic acid compound of the present invention is represented by at least one of the following general formula (1) and general formula (2).
[0033]
Chemistry 3
[0034]
[0035] Here, in the general formula (1), R1 and R3 represent alkylene groups. R2 represents a single bond or an alkylene group. R4 represents an alkylene group. -OCO-A represents an acryloyl group or a methacryloyl group.
[0036]
Chemistry 4
[0037]
[0038] Here, in the general formula (2), R1 and R2 represent an alkylene group. R4 represents an alkylene group. R5 represents a hydrogen atom or an alkyl group. -OCO-A represents an acryloyl group or a methacryloyl group.
[0039] In the general formula (1), the alkylene groups for R1, R2 and R3 are preferably alkylene groups having 1 to 10 carbon atoms, such as methylene, ethylene, propylene, isopropylene, butylene, hexylene, heptylene, octylene, 2-ethylhexylene, tert-octylene and cyclohexylene.
[0040] In the general formula (2), the alkylene groups for R1 and R2 are preferably alkylene groups having 1 to 10 carbon atoms, such as methylene, ethylene, propylene, isopropylene, butylene, hexylene, heptylene, octylene, 2-ethylhexylene, tert-octylene, and cyclohexylene.
[0041] In the general formula (2), the alkyl group represented by R5 is preferably an alkyl group having 1 to 10 carbon atoms, and examples thereof include methyl, ethyl, propyl, isopropyl, butyl, hexyl, heptyl, octyl, 2-ethylhexyl, tert-octyl, and cyclohexyl.
[0042] In the general formula (1) and the general formula (2), the alkylene group of R4 is preferably an alkylene group having 1 to 5 carbon atoms, and examples thereof include methylene, ethylene, propylene, isopropylene, and butylene.
[0043] In the general formula (1), it is preferred that R2 is a single bond, and R1 and R3 are -CH2-. In this case, the hydroxytricarboxylic acid is equivalent to the case of using citric acid for synthesis.
[0044] In the general formula (1) and the general formula (2), R4 is preferably an ethylene group. In this case, the (meth)acrylic acid-modified isocyanate corresponds to the case of using 2-acryloyloxyethyl isocyanate for synthesis.
[0045] The (meth)acryloyl group-containing polycarboxylic acid compound represented by at least one of the general formula (1) and the general formula (2) can be synthesized by applying a (meth)acrylic acid-modified isocyanate to a polycarboxylic acid having a hydroxyl group, as described below.
[0046] <Method for producing a (meth)acryloyl group-containing polycarboxylic acid compound>
[0047] The method for producing the (meth)acryloyl group-containing polycarboxylic acid compound used in the present invention comprises a step of urethanizing a polycarboxylic acid having a hydroxyl group and a (meth)acrylic acid-modified isocyanate, and further comprises other steps as necessary.
[0048] Examples of the polycarboxylic acid having a hydroxy group include hydroxydicarboxylic acid and hydroxytricarboxylic acid.
[0049] Examples of the hydroxydicarboxylic acid include tartaric acid, malic acid, and tartronic acid.
[0050] Examples of the hydroxytricarboxylic acid include citric acid and 1-hydroxy-1,2,3-propanetricarboxylic acid.
[0051] Examples of the (meth)acrylic acid-modified isocyanate include 2-acryloyloxyethyl isocyanate and 2-methacryloyloxyethyl isocyanate.
[0052] As the (meth)acrylic acid-modified isocyanate, a commercially available product may be used, and examples of the commercially available product include 2-acryloyloxyethyl isocyanate (Karenz AOI manufactured by Showa Denko K.K.) and 2-methacryloyloxyethyl isocyanate (Karenz MOI manufactured by Showa Denko K.K.).
[0053] An example of the urethanization reaction of a polycarboxylic acid having a hydroxyl group and a (meth)acrylic acid-modified isocyanate is shown below.
[0054]
Chemistry 5
[0055]
[0056] Here, in the reaction formula, R1 and R3 represent alkylene groups. R2 represents a single bond or an alkylene group. R4 represents an alkylene group. -OCO-A represents an acryloyl group or a methacryloyl group.
[0057] The conditions for the urethanization reaction of the polycarboxylic acid having a hydroxyl group and the (meth)acrylic acid-modified isocyanate are not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include a method of uniformly stirring in a temperature atmosphere maintained at a constant temperature.
[0058] <Other Processes>
[0059] The other steps are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a concentration step and a separation and purification step.
[0060] The polycarboxylic acid compound containing a (meth)acryloyl group represented by at least one of the general formula (1) and the general formula (2) can have both a good fluxing effect and a bonding function as a (meth)acrylic resin. In addition, no reaction occurs during film formation, so that the wettability of the coating liquid is improved. When used as a product, step heating is performed. The fluxing effect is exerted by the first stage of heating. Next, by the second stage of heating, the curing of the polycarboxylic acid compound containing a (meth)acryloyl group begins due to the co-mixed polymerization initiator, and the bonding function and film function as a (meth)acrylic resin are exerted. Furthermore, by combining the curing component and the curing agent, mixed curing can be achieved.
[0061] The first stage heating is preferably performed at 120°C to 150°C, for example.
[0062] The second stage heating is preferably performed at 150°C to 190°C, for example.
[0063] (Heat conduction composition)
[0064] The heat conductive composition of the present invention contains the (meth)acryloyl group-containing polycarboxylic acid compound of the present invention, a curing component, a radical polymerization initiator, heat conductive particles, and low melting point metal particles, and further contains other components as necessary.
[0065] <(Meth)acryloyl-containing polycarboxylic acid compound>
[0066] The content of the (meth)acryloyl-containing polycarboxylic acid compound of the present invention represented by at least one of the general formula (1) and the general formula (2) is not particularly limited and can be appropriately selected according to the purpose, but is preferably 1 volume % to 10 volume % relative to the total volume of the heat conduction composition, and more preferably 1 volume % to 5 volume %
[0067] The (meth)acryloyl group-containing polycarboxylic acid compound of the present invention represented by at least one of the general formula (1) and the general formula (2) can be analyzed by Fourier transform infrared spectroscopy (FT-IR) or the like for the thermal conductive composition before curing.
[0068] <Curing ingredients>
[0069] As the curing component, at least one of an oxirane ring compound and an oxetane compound is preferably used.
[0070] -Oxirane ring compound-
[0071] The oxirane ring compound is a compound having an oxirane ring, and examples thereof include epoxy resins.
[0072] As the epoxy resin, there is no particular limitation, and it can be appropriately selected according to the purpose, and examples thereof include glycidyl ether type epoxy resin, novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A type epoxy resin, trisphenol type epoxy resin, tetraphenol type epoxy resin, phenol-xylylene type epoxy resin, naphthol-xylylene type epoxy resin, phenol-naphthol type epoxy resin, phenol-dicyclopentadiene type epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, etc. These can be used alone or in combination of two or more.
[0073] -Oxetane compounds-
[0074] The oxetane compound is a compound having an oxetane group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound.
[0075] The oxetane compound may be a monofunctional oxetane compound having only one oxetane group, or may be a polyfunctional oxetane compound having two or more oxetane groups.
[0076] The oxetane compound is not particularly limited and can be appropriately selected according to the purpose. Examples thereof include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4-bis(3-ethyl-3-oxetanylmethoxy)butane, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, 6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylenebisoxetane, 4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), bis[(3-ethyl-3-oxetanyl)methyl]isophthalate (OXIPA), etc. These may be used alone or in combination of two or more.
[0077] As the oxetane compound, a commercially available product may be used, and examples of the commercially available product include “ARON OXETANE (registered trademark)” series sold by Toagosei Co., Ltd. and “ETERNACOLL (registered trademark)” series sold by Ube Industries, Ltd.
[0078] Among the above-mentioned oxirane ring compounds and oxetane compounds, preferred are glycidyl ether type epoxy resins, novolac type epoxy resins, cresol novolac type epoxy resins, phenol-dicyclopentadiene type epoxy resins, bisphenol A type epoxy resins, aliphatic epoxy resins, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), and bis[(3-ethyl-3-oxetanyl)methyl]isophthalate (OXIPA).
[0079] The content of the curing component is not particularly limited and may be appropriately selected depending on the intended purpose, but is preferably 0.5 mass % to 60 mass % based on the total amount of the heat conduction composition.
[0080] <Heat-conductive particles>
[0081] As the thermally conductive particles, at least one of copper particles, silver-coated particles, and silver particles is preferred.
[0082] Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles.
[0083] The shape of the thermally conductive particles is not particularly limited and may be appropriately selected depending on the intended purpose. Examples of the shape include spherical, flat, granular, and needle-like particles.
[0084] The volume average particle size of the thermally conductive particles is preferably 10 μm to 300 μm, more preferably 20 μm to 100 μm. If the volume average particle size of the thermally conductive particles is 10 μm to 300 μm, the volume ratio of the thermally conductive particles to the low melting point metal particles can be increased, and high thermal conductivity and low thermal resistance of the thermally conductive composition can be achieved.
[0085] The volume average particle size can be measured, for example, by a laser diffraction / scattering particle size distribution measuring apparatus (apparatus name: Microtrac MT3300EXII, manufactured by Microtrac BEL Co., Ltd.).
[0086] <Low Melting Point Metal Particles>
[0087] As the low melting point metal particles, solder particles specified in JIS Z3282-1999 are preferably used.
[0088] Examples of the solder particles include Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, Sn-Ag-Cu solder particles, etc. These may be used alone or in combination of two or more.
[0089] Among them, solder particles containing Sn and at least one selected from Bi, Ag, Cu, and In are preferred, and Sn—Bi solder particles, Sn—Bi—Ag solder particles, Sn—Ag—Cu solder particles, and Sn—In solder particles are more preferred.
[0090] The shape of the low melting point metal particles is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include spherical, flat, granular, and needle-like shapes.
[0091] The melting point of the low-melting-point metal particles is preferably 100° C. to 250° C., and more preferably 120° C. to 200° C.
[0092] The melting point of the low-melting-point metal particles is lower than the heat curing treatment temperature of the thermally conductive composition, but since the low-melting-point metal particles melt in the cured product of the thermally conductive composition, a network (continuous phase of metal) can be formed through the thermally conductive particles, high thermal conductivity and low thermal resistance can be achieved, which is preferred based on this point.
[0093] The low melting point metal particles react with the heat conductive particles under the heat curing treatment conditions of the heat conductive composition to form an alloy having a higher melting point than the low melting point metal particles, thereby preventing melting at high temperatures and improving reliability. In addition, the heat resistance of the cured product of the heat conductive composition is improved.
[0094] The heat curing treatment of the heat conductive composition is performed, for example, at a temperature of 150° C. to 200° C. for 30 minutes to 2 hours.
[0095] The volume average particle size of the low melting point metal particles is preferably 10 μm or less, more preferably 1 μm or more and 5 μm or less. If the volume average particle size of the low melting point metal particles is 10 μm or less, the volume ratio of the low melting point metal particles to the thermally conductive particles can be reduced, and high thermal conductivity and low thermal resistance of the thermally conductive composition can be achieved.
[0096] The volume average particle size of the low melting point metal particles can be measured in the same manner as the volume average particle size of the thermally conductive particles.
[0097] <Radical Polymerization Initiator>
[0098] Examples of the radical polymerization initiator include aromatic ketones, acylphosphine oxide compounds, aromatic onium salt compounds, organic peroxides, thio compounds (thioxanthone compounds, compounds containing thiophenyl groups, etc.), hexaarylbiimidazole compounds, ketoxime ester compounds, borate compounds, azinium compounds, metallocene compounds, active ester compounds, compounds having a carbon-halogen bond, alkylamine compounds, etc. Among them, organic peroxides are preferred.
[0099] The organic peroxide is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include benzoyl peroxide, lauryl peroxide, t-butyl peroxide, and cumene hydroperoxide.
[0100] The content of the radical polymerization initiator in the heat conduction composition is not particularly limited and may be appropriately selected depending on the intended purpose.
[0101] <Other ingredients>
[0102] The thermal conductive composition may contain other components as long as the effects of the present invention are not impaired. The other components are not particularly limited and can be appropriately selected according to the purpose, and examples thereof include flux components, thermal conductive particles other than metals (such as aluminum nitride, aluminum oxide, carbon fibers, etc.), additives (such as antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc.), etc.
[0103] -Flux ingredients-
[0104] As the flux component, carboxylic acids such as levulinic acid, maleic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, and sebacic acid are preferably used, so that good solder connection can be obtained and the flux can also function as a curing agent of the curing component.
[0105] In addition, as the flux component, a blocked carboxylic acid whose carboxyl group is blocked by an alkyl vinyl ether can be used. This can control the temperature at which the flux effect and curing agent function are exerted. In addition, since the solubility in the resin is improved, the uneven mixing and coating during film formation can be improved.
[0106] The heat conductive composition of the present invention can be prepared by uniformly mixing the (meth)acryloyl group-containing polycarboxylic acid compound of the present invention, a curing component, heat conductive particles, low melting point metal particles, a radical polymerization initiator, and other components as required by a conventional method.
[0107] The thermal conductive composition may be a sheet-like thermal conductive sheet or a paste-like thermal conductive paste (also called a thermal conductive adhesive or thermal conductive paste). Of these, a thermal conductive sheet is preferred due to ease of handling, and a thermal conductive paste is preferred due to cost.
[0108] (Heat conduction sheet)
[0109] The thermally conductive sheet of the present invention comprises a cured product of the thermally conductive composition of the present invention, and is a product obtained by forming the thermally conductive composition of the present invention into a sheet.
[0110] The average thickness of the thermally conductive sheet is preferably 500 μm or less, more preferably 200 μm or less, and further preferably 100 μm or less from the viewpoint of thinning. The lower limit of the average thickness of the thermally conductive sheet is not particularly limited and can be appropriately selected according to the purpose, but is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 50 μm or more.
[0111] The method for producing the thermally conductive sheet is not particularly limited and can be appropriately selected according to the purpose. For example, (1) a method for producing a thermally conductive sheet by molding the thermally conductive composition into a predetermined shape, curing the thermally conductive molded body, and slicing the obtained thermally conductive molded body into a sheet shape, or (2) a method for producing a thermally conductive sheet by forming a cured product layer containing a cured product of the thermally conductive composition on a support having a release layer. In (2), when the thermally conductive sheet is laminated on a heat dissipating substrate, the support is peeled off.
[0112] The thermally conductive composition and thermally conductive sheet of the present invention can be suitably used, for example, as a thermal interface material (TIM1) that allows heat to flow smoothly between a heat source such as an embedded LSI and a heat sink, or when bonding a heat dissipating substrate on which an LED chip or an IC chip is mounted to a heat sink to form a power LED module or a power IC module.
[0113] Here, as the power LED module, there are wire bonding type and flip chip mounting type, and as the power IC module, there is wire bonding type.
[0114] <Heat release structure>
[0115] The heat dissipation structure used in the present invention is composed of a heat generating body, a heat conductive material and a heat dissipation member, and a cured product of the heat conductive composition of the present invention is provided between the heat generating body and the heat dissipation member as the heat conductive material.
[0116] The heating element is not particularly limited and may be appropriately selected depending on the purpose. Examples thereof include electronic components such as a CPU (central processing unit), an MPU (microprocessor), and a GPU (graphics processing unit).
[0117] The heat dissipating member is not particularly limited as long as it is a structure that can dissipate heat generated by the electronic component (heat generating element), and can be appropriately selected depending on the purpose. Examples thereof include a heat sink, a heat sink, a heat spreader, and a heat pipe.
[0118] The heat sink is a component for efficiently transferring the heat of the electronic component to other components. The material of the heat sink is not particularly limited and can be appropriately selected according to the purpose, such as copper, aluminum, etc. The heat sink is usually in the shape of a flat plate.
[0119] The heat sink is a component for releasing the heat of the electronic component into the air. There is no particular limitation on the material of the heat sink, and it can be appropriately selected according to the purpose, such as copper, aluminum, etc. The heat sink, for example, has a plurality of fins. The heat sink, for example, has a base portion and a plurality of fins, and the fins are arranged to extend in a non-parallel direction (for example, a vertical direction) relative to one surface of the base portion.
[0120] The heat sink plate and the heat sink fin are generally solid structures without internal space.
[0121] The heat spreader is a hollow structure. A volatile liquid is sealed in the inner space of the hollow structure. As the heat spreader, for example, a hollow structure such as a plate-shaped hollow structure such as a heat sink having a hollow structure or a heat sink having a hollow structure can be cited.
[0122] The heat pipe is a hollow structure in a cylindrical, substantially cylindrical or flat cylindrical shape, and a volatile liquid is sealed in the inner space of the hollow structure.
[0123] here, Figure 1 The heat conducting composition of the present invention is a cured product (heat conducting sheet) 1 that dissipates heat generated by an electronic component 3 such as a semiconductor element. Figure 1 As shown, the main surface 2a of the heat sink 2 facing the electronic component 3 is fixed to the heat sink 2 and sandwiched between the electronic component 3 and the heat sink 2. In addition, the heat conductive sheet 1 is sandwiched between the heat sink 2 and the heat sink 5. Then, the heat conductive sheet 1 and the heat sink 2 together constitute a heat dissipation member for dissipating the heat of the electronic component 3.
[0124] The heat sink 2 is formed in a square plate shape, for example, and has a main surface 2a facing the electronic component 3 and a side wall 2b rising along the outer periphery of the main surface 2a. The heat sink 2 is provided with a heat conducting sheet 1 on the main surface 2a surrounded by the side wall 2b, and a heat sink 5 is provided on the other surface 2c on the opposite side of the main surface 2a via the heat conducting sheet 1. The higher the heat conductivity of the heat sink 2, the lower the thermal resistance, and the more efficiently the heat of the electronic component 3 such as the semiconductor element is absorbed, so it can be formed using copper or aluminum with good thermal conductivity, for example.
[0125] The electronic component 3 is a semiconductor element such as BGA, and is mounted on the wiring board 6. The heat sink 2 is also mounted on the wiring board 6 at the front end surface of the side wall 2b, thereby surrounding the electronic component 3 at a predetermined distance through the side wall 2b.
[0126] Then, by bonding the thermally conductive sheet 1 to the main surface 2 a of the heat sink 2 , a heat dissipating member is formed that absorbs the heat generated by the electronic component 3 and dissipates the heat from the heat sink 5 .
[0127] [Example]
[0128] Hereinafter, examples of the present invention will be described, but the present invention is not limited to these examples.
[0129] In the following synthesis examples, embodiments and comparative examples, the volume average particle size of the thermally conductive particles and the low melting point metal particles, the FT-IR absorption of the (meth)acryloyl group-containing polycarboxylic acid compound and the 13 C-NMR spectrum determination.
[0130] <Volume Average Particle Diameter of Thermally Conductive Particles and Low Melting Point Metal Particles>
[0131] The volume average particle diameter of the thermally conductive particles and the low melting point metal particles was measured using a laser diffraction / scattering particle size distribution measuring apparatus (apparatus name: Microtrac MT3300EXII, manufactured by Microtrac BEL Co., Ltd.).
[0132] <Measurement of FT-IR Absorption of (Meth)Acryloyl-Containing Polycarboxylic Acid Compound>
[0133] The FT-IR absorption of the (meth)acryloyl group-containing polycarboxylic acid compound was measured by the ATR method using Nicolet iS10 manufactured by Thermo Fisher Scientific.
[0134] <(meth)acryloyl-containing polycarboxylic acid compound 13 C-NMR spectrum determination>
[0135] Polycarboxylic acid compound containing (meth)acryloyl group 13 The C-NMR spectrum was measured using a JNM-ECZ400R / S3 nuclear magnetic resonance apparatus (manufactured by JEOL RESONANCE).
[0136] (Synthesis example 1)
[0137] <Synthesis of Acryloyl-Containing Tricarboxylic Acid Compound>
[0138] In a glass three-necked flask equipped with a thermocouple, a stirring device, a cooling tube and a heating device, 68.0 parts by mass of 2-acryloyloxyethyl isocyanate (Karenz AOI manufactured by Showa Denko K.K.) was added, and 50 parts by mass of 2-butanone (super dehydrated) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added thereto, and stirred thoroughly to completely dissolve. After complete dissolution, 50 parts by mass of citric acid represented by the following structural formula (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was measured and directly dropped into the three-necked flask in a solid form using a funnel. Since side reactions occur when the temperature rises, the temperature was kept constant at 30°C and stirred for 24 hours until the above reaction was completely completed. The obtained synthetic product was cooled at room temperature, transferred to a pear-shaped flask, concentrated with an evaporator, and dried under reduced pressure (at 30°C for 48 hours) to synthesize the target acryloyl-containing tricarboxylic acid compound (yield 93%). In addition, the FT-IR absorption of the acryloyl group-containing tricarboxylic acid compound obtained in Synthesis Example 1 was measured to confirm peaks before and after synthesis, and a peak of NCO (about 2270 cm -1 ~2240cm -1 ) all disappear.
[0139] [Citric acid]
[0140]
Chemistry 6
[0141]
[0142] <Identification Data>
[0143] The FT-IR absorption of the acryloyl group-containing tricarboxylic acid compound of Synthesis Example 1 is shown below.
[0144] 809cm -1 , 982cm -1 , 1064cm -1 , 1181cm -1 , 1268cm -1 , 1408cm -1 , 1557cm -1 , 1713cm -1 and 2700cm -1 ~3700cm -1 A broad absorption vibration from carboxylic acid is visible above.
[0145] Regarding the acryloyl group-containing tricarboxylic acid compound obtained in Synthesis Example 1 13 The peaks of C-NMR are shown below.
[0146] 13C-NMR (CDCl3, δppm); 39.49(15), 39.83(15), 40.13(3;8), 40.46(3,8), 40.79(3;8), 62.08(16), 62.44(16), 62.80(1 6), 76.75(2), 127.82(22)131.10(23), 131.51(23), 131.92(23), 154.27(6), 165.71(18), 173.05(11), 173.34(4;9)
[0147] Above 13 The numbers of the parts described in parentheses in the C-NMR peaks are as follows.
[0148]
Chemistry 7
[0149]
[0150] (Synthesis example 2)
[0151] <Synthesis of Methacryloyl-Containing Tricarboxylic Acid Compound>
[0152] In Synthesis Example 1, except that 2-acryloyloxyethyl isocyanate (Karenz AOI, manufactured by Showa Denko K.K.) was replaced with 2-methacryloyloxyethyl isocyanate (Karenz MOI, manufactured by Showa Denko K.K.), a methacryloyl group-containing tricarboxylic acid compound was synthesized in the same manner as in Synthesis Example 1 (yield 93%). In addition, the FT-IR absorption of the obtained methacryloyl group-containing tricarboxylic acid compound of Synthesis Example 2 was measured, and peaks before and after the synthesis were confirmed. The peak of NCO (about 2270 cm -1 ~2240cm -1 ) all disappear.
[0153] <Identification Data>
[0154] The FT-IR absorption of the methacryloyl group-containing tricarboxylic acid compound of Synthesis Example 2 is shown below.
[0155] 810cm -1 , 983cm -1 , 1067cm -1 , 1126cm -1 , 1182cm -1 , 1270cm -1 , 1336cm -1 , 1408cm -1 , 1566cm -1 , 1634cm -1 , 1703cm -1 and 2700cm-1 ~3700cm -1 A broad absorption vibration from carboxylic acid is visible above.
[0156] Regarding the methacryloyl-containing tricarboxylic acid compound obtained in Synthesis Example 2 13 The peaks of C-NMR are shown below.
[0157] 13 C-NMR (CDCl3, δppm); 17.75(23), 39.26(15), 39.60(15), 40.13(3;8), 40.46(3;8), 40.79(3;8), 62.48(16), 62.84(1 6), 63.20(16), 76.75(2), 125.52(24), 125.92(24), 126.32(24), 135.76(22), 166.52(18), 173.05(11), 173.34(4;9)
[0158] Above 13 The numbers of the parts described in parentheses in the C-NMR peaks are as follows.
[0159]
Chemistry 8
[0160]
[0161] (Synthesis example 3)
[0162] <Synthesis of Acryloyl-Containing Dicarboxylic Acid Compound>
[0163] In Synthesis Example 1, except that 50 parts by mass of citric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was replaced with 26.6 parts by mass of L(+)-tartaric acid (manufactured by Kanto Chemical Co., Ltd.) represented by the following structural formula, an acryloyl group-containing dicarboxylic acid compound was synthesized in the same manner as in Synthesis Example 1 (yield 93%). In addition, the FT-IR absorption of the acryloyl group-containing dicarboxylic acid compound of Synthesis 3 was measured, and peaks before and after the synthesis were confirmed. The peak of NCO (about 2270 cm -1 ~2240cm -1 ) all disappear.
[0164] [tartaric acid]
[0165]
Chemistry 9
[0166]
[0167] <Identification Data>
[0168] The FT-IR absorption of the acryl group-containing dicarboxylic acid compound of Synthesis 3 is shown below.
[0169] 810cm -1 , 987cm -1 , 1081cm -1 , 1121cm -1 , 1218cm -1 , 1383cm -1 , 1409cm -1 , 1634cm -1 , 1722cm -1 and 2700cm -1 ~3700cm -1 A broad absorption vibration from carboxylic acid is visible above.
[0170] Regarding the acryloyl group-containing dicarboxylic acid compound of the obtained synthetic product 3 13 The peaks of C-NMR are shown below.
[0171] 13 C-NMR (CDCl3, δppm); 40.03 (20; 40), 61.99 (21; 15), 62.35 (21; 15), 62.71 (21; 15), 73.62 (2; 3), 73.99 (2;3), 127.82(29;27), 131.10(30;28), 131.51(30;28), 131.92(30;28), 154.11(7;5), 170.61(9;11)
[0172] Above 13 The numbers of the parts described in parentheses in the C-NMR peaks are as follows.
[0173]
Chemistry 10
[0174]
[0175] (Example 1)
[0176] 3.26 volume % of the acryl-containing tricarboxylic acid compound of Synthesis Example 1 as a base resin, 2.24 volume % of a low melting point flux (P303K, manufactured by Dexerials Co., Ltd.) and 2.24 volume % of an oxetane compound (OXBP, manufactured by UBE Co., Ltd.) were added, and further, 56.30 volume % of Ag-coated Cu particles (manufactured by Fukuda Metal Foil Powder Co., Ltd., volume average particle size Dv: 40 μm) as thermally conductive particles and 1.5 volume % of Sn as low melting point metal particles were added. 58 Bi 4235.96% by volume of particles (Mitsui Mining & Smelting Co., Ltd., volume average particle size Dv: 4 μm) were uniformly mixed with a stirring device (Awatori Rentaro automatic rotary mixer, manufactured by Thinky Co., Ltd.). Furthermore, 0.025% by volume of a free radical polymerization initiator (PEROYLTCP, manufactured by NOF Corporation) was added and stirred thoroughly to prepare the heat transfer composition of Example 1.
[0177] The obtained thermally conductive composition was applied onto a 38 μm thick release film (38GS, manufactured by Lintec Corporation) by bar coating, heated at 80° C. for 15 minutes, and dried to prepare a thermally conductive sheet having an average thickness of 100 μm.
[0178] (Example 2)
[0179] In Example 1, a thermally conductive composition and a thermally conductive sheet of Example 2 were prepared in the same manner as in Example 1, except that the acryl group-containing tricarboxylic acid compound of Synthesis Example 1 was replaced with the methacryloyl group-containing tricarboxylic acid compound of Synthesis Example 2.
[0180] (Example 3)
[0181] In Example 1, a heat conductive composition and a heat conductive sheet of Example 3 were prepared in the same manner as in Example 1, except that the acryl group-containing tricarboxylic acid compound of Synthesis Example 1 was replaced with the acryl group-containing dicarboxylic acid compound of Synthesis Example 3.
[0182] (Example 4)
[0183] In Example 1, a thermally conductive composition and a thermally conductive sheet of Example 4 were prepared in the same manner as in Example 1, except that the content of the acryl group-containing tricarboxylic acid compound in Synthesis Example 1 was changed from 3.26% by volume to 1% by volume.
[0184] (Example 5)
[0185] In Example 1, a heat conductive composition and a heat conductive sheet of Example 5 were prepared in the same manner as in Example 1 except that the content of the acryl group-containing tricarboxylic acid compound in Synthesis Example 1 was changed from 3.26% by volume to 10% by volume.
[0186] (Comparative Example 1)
[0187] In Example 1, the thermally conductive composition and thermally conductive sheet of Comparative Example 1 were prepared in the same manner as in Example 1, except that 3.26% by volume of the acryl-containing tricarboxylic acid compound in Synthesis Example 1 was changed to 3.26% by volume of M-1276 (polyamide resin, manufactured by Arkema Co., Ltd.) and no free radical polymerization initiator (PEROYL TCP, manufactured by NOF Corporation) was added.
[0188] (Comparative Example 2)
[0189] In Example 1, a thermally conductive composition and a thermally conductive sheet of Comparative Example 2 were prepared in the same manner as in Example 1, except that 3.26% by volume of the acryl group-containing tricarboxylic acid compound in Synthesis Example 1 was changed to 3.26% by volume of an acrylic monomer (UA-306H, manufactured by Kyoeisha Chemical Co., Ltd.).
[0190] <Production of Cured Material>
[0191] Next, a 0.125 mm partition was set between two 30 mm × 30 mm × 2 mm aluminum plates (A5052P), and each heat conductive composition punched out to a diameter of 20 mm was sandwiched therebetween. The heat conductive compositions were oven-cured at 150° C. for 60 minutes to obtain cured products (interface Al) of the heat conductive compositions.
[0192] Next, the adhesiveness and thermal conductivity of each of the obtained cured products were evaluated as follows.
[0193] <Adhesion>
[0194] The cured product of each heat conduction composition was heated on a hot plate heated to 130° C. for 1 minute, the peeling state was confirmed, and the adhesiveness was evaluated based on the following criteria.
[0195] [Evaluation criteria]
[0196] A: Unable to peel off two aluminum plates
[0197] B: Can be peeled off using pliers etc.
[0198] C: When two aluminum plates are staggered, they can be easily peeled off
[0199] <Thermal conductivity>
[0200] A 0.125 mm spacer was placed between two 30 mm × 30 mm × 2 mm copper plates, and each heat conductive composition punched out to a diameter of 20 mm was sandwiched therebetween. The heat conductive compositions were oven cured at 150°C for 60 minutes. The cured product (interface Cu) of each heat conductive composition was measured for thermal resistance (°C·cm) by a method based on ASTM-D5470. 2 / W). The thermal resistance of the copper plate was removed from the result to calculate the thermal resistance of the cured product. The thermal conductivity (W / m·K) was determined from the thermal resistance and the thickness of the cured product and evaluated according to the following criteria.
[0201] [Evaluation criteria]
[0202] A: Thermal conductivity is 11.0W / m·K or more
[0203] B: Thermal conductivity is 8.0 W / m·K or more and less than 11.0 W / m·K
[0204] C: Thermal conductivity is less than 8.0 W / m·K
[0205]
Table 1
[0206]
[0207]
Table 2
[0208]
[0209] The details of each component in Table 1 and Table 2 are as follows.
[0210] *Acrylic monomer: UA-306H, manufactured by Kyoeisha Chemical Co., Ltd., pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer
[0211] *Polyamide resin: M-1276, manufactured by Arkema Co., Ltd.
[0212] *P303K: Low melting point flux, manufactured by Dexerials Co., Ltd.
[0213] *OXBP: oxetane compound, manufactured by UBE Corporation, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl
[0214] *Heat conductive particles: Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., volume average particle size Dv: 40 μm
[0215] *Low melting point metal particles: Sn 58 Bi 42 Particles, manufactured by Mitsui Mining and Smelting Co., Ltd., volume average particle size Dv: 4 μm
[0216] *Free radical polymerization initiator: PEROYL TCP, manufactured by NOF Corporation
[0217] [Possibility of Industrial Application]
[0218] The heat conductive composition and heat conductive sheet of the present invention using the (meth)acryloyl group-containing polycarboxylic acid compound of the present invention can exhibit high adhesive strength and good fluxing effect, and can achieve high thermal conductivity. Therefore, they are suitable for use in, for example, various electrical equipment such as CPUs, MPUs, power transistors, LEDs, laser diodes, various batteries (various secondary batteries such as lithium ion batteries, various fuel cells, capacitors, amorphous silicon, crystalline silicon, compound semiconductors, various solar cells such as wet solar cells, etc.) where temperature has an adverse effect on the efficiency and life of the operation of the components, and in the vicinity of heat sources of heating equipment that require effective use of heat, heat exchangers, and heat pipes of floor heating devices.
[0219] This international application claims the benefit of priority based on Japanese Patent Application No. 2022-140623 filed on September 5, 2022, the entire contents of which are incorporated herein by reference.
[0220] [Reference Signs]
[0221] 1 Thermally conductive material (thermally conductive sheet)
[0222] 2 Heat dissipation components (heat sink)
[0223] 2a Main side
[0224] 3. Heat generating element (electronic components)
[0225] 3a Upper surface
[0226] 5. Heat dissipation components (heat sink)
[0227] 6 Wiring substrate
Claims
1. A polycarboxylic acid compound containing a (meth)acryloyl group, characterized in that: is represented by at least one of the following general formula (1) and the following general formula (2), 【Chemistry 1】 Wherein, in the general formula (1), R1 and R3 represent alkylene groups, R2 represents a single bond or an alkylene group, R4 represents an alkylene group, -OCO-A represents an acryloyl group or a methacryloyl group, 【Chemistry 2】 In the general formula (2), R1 and R2 represent alkylene groups, R4 represents an alkylene group, R5 represents a hydrogen atom or an alkylene group, and -OCO-A represents an acryloyl group or a methacryloyl group. 2 . The (meth)acryloyl-containing polycarboxylic acid compound according to claim 1 , wherein in the general formula (1), R2 is a single bond, and R1 and R3 are -CH2-. 3 . The (meth)acryloyl group-containing polycarboxylic acid compound according to claim 1 , wherein R 4 is an ethylene group. 4 . The (meth)acryloyl group-containing polycarboxylic acid compound according to claim 1 , which has flux activity.
5. A heat conduction composition, characterized in that: A composition comprising the (meth)acryloyl group-containing polycarboxylic acid compound according to any one of claims 1 to 4, a curing component, a radical polymerization initiator, thermally conductive particles and low-melting-point metal particles. 6 . The heat conduction composition according to claim 5 , wherein the content of the (meth)acryloyl group-containing polycarboxylic acid compound is 1% by volume or more and 10% by volume or less.
7. The heat transfer composition according to any one of claims 5 to 6, wherein the curing component is at least one of an oxirane ring compound and an oxetane compound. 8 . The thermally conductive composition according to claim 5 , wherein the thermally conductive particles are at least one of copper particles, silver-coated particles, and silver particles. 9 . The heat conduction composition according to claim 5 , wherein the low melting point metal particles contain Sn and at least one selected from Bi, Ag, Cu and In.
10. A heat conduction sheet, characterized in that: A cured product comprising the heat conduction composition according to any one of claims 5 to 9.
Citation Information
Patent Citations
Overmolding Techniques for Peel-Away Introducer Design
JP2022140623A